ANALISIS KLASTERING DAMPAK LINGKUNGAN BERDASARKAN KONSUMSI ENERGI PERUSAHAAN BERBASIS INDUSTRI 4.0 MENGGUNAKAN METODE CRISP-DM - Kusuma, Dewa Adji; Putro, Aditya Dwi (P3M Politeknik Negeri Banjarmasin, 2023)
The growth of energy consumption worldwide has experienced a significant increase in the past two decades. The increase in energy consumption in a company indicates that the company generates more carbon dioxide (CO2) emissions than usual. Excessive carbon emissions have a significant impact on human health and the environment. According to the World Health Organization (WHO), greenhouse gas emissions resulting from the extraction and combustion of fossil fuels are major contributors to climate change and air pollution. It is necessary to analyze what factors contribute to high carbon emissions. This study uses the CRISP-DM (Cross-Industry Standard Process for Data Mining) method. The K-Means algorithm will be used to cluster the features that influence high carbon emissions. The feature selection process for K-Means uses Pearson correlation. The clustering model results in good evaluation scores using the Silhouette evaluation metric. Subset data 1 obtained a Silhouette score of 0.744, and subset data 2 obtained a Silhouette score of 0.7629. The evaluation results indicate that the K-Means model works quite well in creating clusters.